A Dilemma Between the Use of the Land and the Right of Prior Consultation in Colombia: The Dispute for the Land of the resguardos - Mora Vera, Germán Andrés (Reflexión Política, 2017)
This article constitutes one contribution to the analysis of the conflict between the indigenous people and the governments through history in Colombia over the lands of resguardos or native indigenous reservation areas, focusing the attention in the legal and political framework that rules these ethnic minorities' rights and especially the right of prior consultation; understood as one of the reasons which has intensified the conflict between both parties in time specifically from the decade of the 1990s. This study considers that this dispute between these both parties is not only caused due to the contrary visions and perspectives over the land –and over the natural resources present in it– but also due to the presence of contradictions in the laws, policies, norms, decrees, etc., as the factors which have not only extended for more than 400 years but also intensified the dispute amid these two parties to the present day.